Вплив наночастинок золота на кріоконсервовані мезенхімальні стовбурові клітини - Волкова, Н. О.; Юхта, М. С.; Гольцев, А. М. (Наносистеми, наноматеріали, нанотехнології 2022; 20 (1): 249–261, 2022)
Сумісне застосування наночастинок і стовбурових клітин може значно поліпшити результати терапії, і хоча потенціял цього є значним, все ще є багато проблем, які необхідно вирішити, перш ніж прийняти їх до клінічного застосування. В дослідженні проведено порівняльну оцінку морфофункціональних характеристик кріоконсервованих мезенхімальних стовбурових клітин (КрМСК) з жирової та хрящової тканин за умов взаємодії їх із наночастинками золота (AuNPs). КрМСК з досліджених джерел інкубували з AuNPs у скінченних концентраціях 4, 6, 10, 20 мкг/мл протягом 1 години, після чого оцінювали цілісність мембрани, стан процесів апоптозу/некрозу, морфологічні характеристики та проліферативну активність. Контролем були КрМСК без впливу AuNPs (0 мкг/мл). Встановлено, що AuNPs у концентраціях 4 та 6 мкг/мл не впливали на цілісність мембрани, проліферативну активність і процеси апоптозу/некрозу в КрМСК із жирової та хрящової тканин. AuNPs у концентрації 10 мкг/мл призводили до пониження показника цілісности мембрани, проліферативної активности, а також збільшення відсотка клітин у стані апоптозу в КрМСК з жирової тканини. При застосуванні AuNPs у концентрації 20 мкг/мл визначали пониження кількости клітин з цілісною мембраною, проліферативної активности їх та збільшення відсотка клітин у стані апоптозу/некрозу в КрМСК з жирової та хрящової тканин. Одержані результати можуть бути використані для обґрунтування та розробки методик застосування КрМСК у поєднанні з AuNPs у клінічній практиці для лікування уражень тканин опорно-рухового апарату _________________________________________________________________________________________ A combined use of nanoparticles and stem cells can significantly improve the results of therapy, and although their potential is significant, there are still many problems, which are need to be solved before they can be accepted for clinical use. The study carried out a comparative assessment of the morphological and functional characteristics of cryopreserved mesenchymal stem cells (CrMSCs) from adipose and cartilaginous tissues in the conditions of their interaction with gold nanoparticles (AuNPs). CrMSCs cells from the studied sources were incubated with AuNPs at final concentrations of 4, 6, 10, 20 μg/ml for 1 hour, after that the integrity of the membrane, the state of apoptosis/necrosis processes, morphological characteristics, and proliferative activity are assessed. The control is CrMSCs without the influence of AuNPs (0 μg/ml). As found, 4 and 6 μg/ml AuNPs in CrMSCs of the adipose and cartilage tissues did not affect studied parameters. The cell viability is decreased in adipose-derived CrMSCs incubated with 10 and 20 μg/ml AuNPs and in cartilage-derived CrMSCs incubated with 20 μg/ml AuNPs. Using of 10 and 20 μg/ml AuNPs also results in an increase in the amount of Annexin V+/7AAD- adipose-derived CrMSCs by 1.6 and 2.4 times, respectively, relative to a control. The percentage of Annexin V+/7AAD+ + Annexin V-/7AAD+ adipose-derived CrMSCs exceeds the corresponding control value by 1.3 times when incubated with 20 μg/ml AuNPs. An increase in the number of cartilage-derived CrMSCs in the state of early apoptosis and late apoptosis/necrosis is observed by 1.3 and 2 times, respectively, after incubation with 20 μg/ml AuNPs. The results of light microscopy show that 10 and 20 μg/ml AuNPs lead to a decrease in proliferative activity and changes in the morphological characteristics (cytoskeletal dystrophy, cytoplasmic granulation, and nuclei vacuolization) of adipose-derived CrMSCs relative to a control. In cultures of cartilage-derived CrMSCs, a decrease in proliferative activity and morphological changes (cytoskeleton degenerative changes, detachment of cells) are observed only after incubation with 20 μg/ml AuNPs. The obtained results can be used to substantiate and develop methods of combined use of CrMSCs and AuNPs in clinical practice for the treatment of tissue damages of the musculoskeletal system.
Волкова, Н. О., Юхта, М. С., Гольцев, А. М. Вплив наночастинок золота на кріоконсервовані мезенхімальні стовбурові клітини. Наносистеми, наноматеріали, нанотехнології 2022; 20 (1): 249–261
Keywords: наночастинки золота; кріоконсервовані мезенхімальні стовбурові клітини; жирова тканина; хрящова тканина; проліферація; апоптоз; некроз; _________________________________________________________________________; gold nanoparticles; cryopreserved mesenchymal stem cells; adipose tissue; cartilage tissue; proliferation; apoptosis; necrosis